The Role of Artificial Intelligence in Improving Production Planning: An Analytical Survey Study in The Nineveh Governorate Electricity Distribution Department - Hazem Seltun, Walaa (Iraqi Journal for Administrative Sciences, 2026)
Through the current study, we seek to investigate and analyze artificial intelligence and its impact on improving production planning. This research aims to shed light on the role of artificial intelligence in improving the efficiency and effectiveness of production planning within industrial enterprises. The abstract demonstrates how the application of artificial intelligence contributes to forecasting demand, improving production scheduling, reducing waste, and increasing the ability to adapt to market and internal variables. It also discusses the fundamental differences between traditional methods and methods supported by artificial intelligence. In addition to the potential challenges in implementing these technologies, our current study, implemented in the Nineveh Electricity Distribution Department, relied on a questionnaire as the primary tool for collecting data and information, in addition to personal interviews with electricity distribution branch officials, observations, and field observations. (50) questionnaires were distributed and all returned. The study reached a number of conclusions, the most prominent of which is "Improving the efficiency of resource use. Through its ability to process large amounts of data, artificial intelligence enables a more effective allocation of resources (materials, machinery, and labor), leading to reduced waste and increased productivity."